Development Of E-Modules For Prayer Practice Using Flip PDF Professional - Muchlis Mudzofar; Abas Mansur Tamam (AL-WIJDÃN Journal of Islamic Education Studies, 2023)
This study aims to produce electronic prayer practice modules using the Flip PDF Professional application. The research was conducted in the form of research and development (R&D). The development model used is the ADDIE model (analysis, design, development, implementation, and evaluation). The electronic module developed by the author contains material presented using images, videos, audio, and animation to increase students' interest in learning the practice of prayer and effectiveness in the learning process. The results showed that the electronic module developed had met the required standards. Validation was carried out by material experts, media experts, and linguists. In addition, the electronic module has also been field tested on a small scale by 8 learners and a large scale by 15 learners. The interpretation of the material expert shows that this e-module is very feasible with a percentage score of 87.50%, the interpretation of the language expert shows feasibility with a percentage score of 89.58%, and the interpretation of the media expert shows feasibility with a percentage score of 80.27%. The results of the field trial also showed that this e-module received a good assessment with a percentage score of 82.50%. Based on the results of the trial, it can be concluded that the electronic module of prayer practice is included in the good category and received positive responses from experts, students, and teachers. Currently, the implementation of the electronic prayer module in the learning process is being carried out, and the results of this research will be published in the next article   Keywords: Electronic Modules, Flip PDF Professional, Prayer, Worship